Media-socialization: gender stereotypes of serial reality - Voznesenska О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
This article contains partial results of the empirical study of images of characters, which have crucial influence on gender socialization. Typical stereotypical images of soap opera heroes are selected. It is concluded that distortions in gender behavioral models among children of primary school age occur due to the specifics of the media socialization process.